Pertumbuhan dan Produksi Tiga Varietas Kacang Hijau (Phaseolus Radiatus. L) pada Beberapa Jarak Tanam di Lahan Gambut - Anthony Hamzah; Rosmimi '; Syamsuardi ' (Jurnal Sagu, 2005)
The objective ofthis research was to determine tJic effect of planting distance on the growth and production ofseveral mung bean varieties cultivated in peat soil. The research was conducted in Tiiah Karya area Sub-District ofSimpangBaru of Panam District. The research method was Randomized Klock Dcsijin (RB1» withthree replications. The data obtained were analysed by ANOVA and continued by LSD at the level of 5 %. Theresult shows that each mung bean variety exhibited a different response when planted in the peal soil withvarious planting d'islance. The best growth of the third varieties was found when cultivated in the plantingdistance of35 x 35 an (J3), and the highest production was observed in the planting distance of 25 x 25 cm (J 1).Variety No.l29 yielded bean of 1,2 ton per hectare when cultivated in the peat soil with planting distanceof 25 X 25 cm.